Digital Counter-Radicalism: The Strategic Role of Religious Organisations in Shaping Moderate Islam in Indonesia’s Cyber Realm - Dadang Kuswana (Khazanah Theologia, 2024)
Purpose: This study investigates the digital strategies employed by Nahdlatul Ulama (NU) and Muhammadiyah, two of Indonesia's largest moderate Islamic organisations, in countering radicalism on social media. The research aims to evaluate the effectiveness of these strategies in reaching and influencing the younger generation, particularly in the context of growing radical content online. Methodology: A qualitative approach was utilised, involving direct observation of social media content, in-depth interviews with key figures from NU and Muhammadiyah, and a review of relevant literature. The study also included interviews with Generation Z students to gauge their responses to the digital strategies of these organisations. Findings: The study found that NU's innovative approach, particularly through creative social media campaigns like "Merah Putih vs. Radikalisme" on YouTube, has been more effective in capturing broad public attention and reinforcing moderate Islamic narratives. In contrast, Muhammadiyah's more relaxed approach, while meaningful, has not achieved the same level of impact among younger audiences. However, Muhammadiyah's digital applications like SalamMu and Edumu contribute significantly to promoting moderate Islam and countering radical influences. Research Implications: The findings underscore the importance of continuous innovation in digital strategies for religious organisations to maintain relevance and effectiveness in combating radicalism. The study suggests that both NU and Muhammadiyah need to refine their approaches further to better engage with the younger generation, who are more susceptible to radical ideologies online. Originality/Value: This research contributes to the understanding of the intersection between religion and digital technology in a predominantly Muslim society. It provides unique insights into how moderate Islamic organisations can leverage social media to counter radicalism and foster a culture of tolerance and inclusivity in the digital age. The study also highlights the potential and limitations of current strategies, offering a foundation for future research and policy development in digital counter-radicalism efforts.